2015
DOI: 10.3906/zoo-1403-24
|View full text |Cite
|
Sign up to set email alerts
|

Helminths of the digestive tract in Buteo buteo (Falconiformes: Falconidae)in Bursa Province of Northwest Turkey

Abstract: IntroductionTurkey has 97 Important Bird Areas (IBAs), which cover a total of 29.978 km 2 , or 4% of the total land area. The country is divided into 7 major geographical regions, each with different climates, habitats, flora, and fauna. The study area, Bursa, is located along the Marmara Sea. This province, which lies along migratory flyways, is an important transit area for migratory birds and contains 4 IBAs (Magnin et al., 2000).Members of the genus Buteo are primarily residents or short-distance migrants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Most of the pathogens identified in this study are commonly found in European diurnal and nocturnal raptors [8,23,24,30,35,[37][38][39][40][41][42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the pathogens identified in this study are commonly found in European diurnal and nocturnal raptors [8,23,24,30,35,[37][38][39][40][41][42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the available information, most of these previous studies were restricted to sole reports of parasite presence in a certain species, with small sample sizes [1][2][3][4][13][14][15]18,31,32]. In these studies, parasite species differentiation was based on morphological features only.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that white storks, like some other migratory birds, are under protection and, therefore, their hunting is prohibited throughout the year. Thus, there are only a few studies about the intestinal helminths of some wild birds in Turkey (Umur et al, 2010;Tezel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%